2022
DOI: 10.1038/s41598-022-12148-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and source identification for heavy metals in surface sediments of East Dongting Lake, China

Abstract: Dongting Lake is one of the most important inland freshwater lakes in China. To investigate the spatial distribution and seasonal variation characteristics of heavy metals (Cr, Co, Cu, Zn, Cd, and Pb) in the lake, 53 surface sediment samples were collected in the East Dongting Lake (ED Lake) in the wet and dry seasons. Results show Cr, Co, Cu, Zn, Cd, and Pb contents were 1.7 (1.9), 1.8 (2.0), 2.9 (3.0), 1.9 (1.9), 11.7 (13.1), and 2.0 (2.2)-fold of their geochemical soil background values of Hunan province (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…Heavy element contamination directly threatens both human life and the environment. They are transferred to people via the food chain and by drinking contaminated water (Huang et al 2020) since these components are undegraded chemically or biologically and persist in soil and sediments for extended periods (Yuan, Liu & Liu, 2022). Heavy element concentrations above normal levels disturb the biological balance of the soil and lower its fertility (Barbieri, 2016), resulting in a reduction in land usage for agricultural production, which poses a danger to food insecurity (Rai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy element contamination directly threatens both human life and the environment. They are transferred to people via the food chain and by drinking contaminated water (Huang et al 2020) since these components are undegraded chemically or biologically and persist in soil and sediments for extended periods (Yuan, Liu & Liu, 2022). Heavy element concentrations above normal levels disturb the biological balance of the soil and lower its fertility (Barbieri, 2016), resulting in a reduction in land usage for agricultural production, which poses a danger to food insecurity (Rai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of sediments is a signi cant environmental indicator of water pollution (Tokatli 2019), as sediments are a nal or temporary sink for various types of pollutants, including the elements discharged to the environment (Chen et al 2022). The sediments of valleys and rivers are exposed to pollution with heavy metals transported from various natural and anthropogenic sources (Yuan, Liu & Liu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of sediments is a signi cant environmental indicator of water pollution (Gargouri et al, 2018;Tokatli, 2019), as sediments are a nal or temporary sink for various types of pollutants, including the elements discharged to the environment (Saydam Eker, 2020; Chen et al, 2022). The sediments of valleys and rivers are exposed to pollution with H.M.s transported from various natural and anthropogenic sources (Dhamin and Majeed, 2022;Yuan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…H.M.s contamination directly threatens both human life and the environment. They are transferred to people via the food chain and by drinking contaminated water (Huang et al, 2020;Nkwunonwo et al, 2020) since these components are undegraded chemically or biologically and persist in soil and sediments for extended periods (Yuan, Liu & Liu, 2022). H.M.s contents above normal levels disturb the biological balance of the soil and lower its fertility (Barbieri, 2016;Skorbiłowicz et al, 2021;Zhao et al 2022) resulting in a reduction in land usage for agricultural production, which poses a danger to food insecurity (Kopittke et al 2019;Rai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals in the environment that flow with river flows from upstream to downstream can accumulate in sediments through adsorption and deposition processes (Zhang et al, 2022) so that they can be found in estuary sediments with high concentrations. There is the potential for heavy metals in the sediment to be released back into the water column which can cause secondary contamination in the water column, this is influenced by hydrodynamic conditions and environmental factors (Yuan et al, 2022). The hydrodynamic conditions and environmental factors in the Citarum River estuary are different from the river water bodies.…”
Section: Introductionmentioning
confidence: 99%